Preserving the Physical Coupling in Teleoperation despite Time Delay through Observer-Based Gradient Control. Issue 18 (2019) - Singh, Harsimran; Panzirsch, Michael; Ryu, Jee-Hwan
Abstract: In recent past, a variety of control approaches were proposed that serve the stabilization of coupled network systems despite time delay. Especially in teleoperation setups, where the input device displays the interaction forces and torques of the remote coupled robot with its environment to a human operator. This force feedback should represent the physical behavior of a coupling at zero time delay. However, most control approaches aim to limit the force feedback for the sake of stability which does not necessarily lead to a reasonable presentation of the remote side impedances. Recently, Singh et al. (2019) proposed an observer-based gradient controller to eliminate the force jittering on the master side. It rectified the delayed feedback force by removing the undesired increase in force which is generated by the delay in communication channel. The stability of the system was assured via the Time Domain Passivity Approach which leads to an undesired position drift. In this work the observer-based gradient approach is modified to increase it's force transparency and implemented to another recently developed position-drift free Time Domain Passivity Approach, Panzirsch et al. (2019). The new amalgamated approach is validated and compared to the state-of-the-art in experiments.